The cryoconservation of seed materials of Serratula kirghisorum - Dodonova А.Sh.; Gavrilkova, E.N.; Ishmuratova М.Yu.; Tleukenova, S.U.; Verzhuk, V.G.; Pavlov, A.V. (Fundamental and Experimental Biology, 2016)
Seed germination and viability of seed material of Serratula kirghisorumof various methods of cryoconservation are studied; influence of a container, a method of freezing and defrosting, application of cryoprotectors is defined. The best indicators have been received at use of glycerin as cryoprotector, plastic test tubes. Thawing of seed material needed to be carried out quickly with application of a hot water bath. The biology of germination of seed material at various methods of cryodeposition is studied. Essential distinctions in biology germination of seeds after a cryopreservation aren’t revealed. The sprout passed all phases of development; the sizes of the main parts of sprout had not considerable differences. After freezing in liquid nitrogen passing by a sprout of phases of development happened slightly quicker, on average for one day, besides sprouts were more viable and strong. All results testified about safety of a cryopreservation for a seed germ, and allowed to use this method for preservation of seed material during creation of a collection of endemic plants’ seeds.